Best Website of Practices by Malaysian Environmental NGOs: A Comparative Study - Abdullah, Aida Nasirah; Hussin, Hanipah; Hasan, Hazmilah; Kalthom, Hussain; Aziz , Yahya (Penerbit Universiti, UTeM, 2010)
This research is the first attempt to cover best practices for environmental websites in Malaysia. We choose five environmental NGOs in Malaysia (ENGOMs) for a case study and evaluated website practices they used to communicate their missions and goals. A quantitative data was collected and analyzed via content analysis of the five ENGOM websites. The content analysis of the websites sought to determine, identify and assess the best practices of the environmental issues and potentially mobilize government or public action on these issues. How do the ENGOMs effectively use the website to communicate their organizations' missions goals?